Mapping multiplexing technique (MMT): a novel intensity modulated transmission format for high-speed optical communication systems - Mohamed Elsherif, Mohamed Assad Hashem (2016)
There is a huge rapid growth in the deployment of data centers, mainly driven from the increasing demand of internet services as video streaming, e-commerce, Internet Of Things (IOT), social media, and cloud computing. This led data centers to experience an expeditious increase in the amount of network traffic that they have to sustain due to requirement of scaling with the processing speed of Complementary metal–oxide–semiconductor (CMOS) technology. On the other side, as more and more data centers and processing cores are on demand, as the power consumption is becoming a challenging issue. Unless novel power efficient methodologies are innovated, the information technology industry will be more liable to a future power crunch. As such, low complex novel transmission formats featuring both power efficiency and low cost are considered the major characteristics enabling large-scale, high performance data transmission environment for short-haul optical interconnects and metropolitan range data networks.